Spinal shape analysis in 1,020 healthy young adults aged from 19 to 30 years - Jakub Krejčí; Jiří Gallo (Palacký University Olomouc, 2016)
Background: A number of studies on diseased spine have been published; however, there is a relative paucity of studies investigating spine shape characteristics in healthy populations. Such characteristics are needed for diagnostics of spine disorders and assessment of changes in the spinal shape that may have been caused by influence of the modern life style or intensive sport activity. Objective: The aim of the study was to determine characteristics of the spine shape in a large sample of healthy young adults. Methods: Population cross-sectional study. A non-radiographic surface method (system DTP-3) was used for the assessment of spine shape in the sagittal and frontal planes. A total of 1,020 participants (440 men, 580 women) took part in the study, their mean (± SD) age was 21.8 ± 1.9 years (range 19.1-29.7) for men and 21.9 ± 1.8 years (range 19.3-29.7) for women. All data were checked for normality and are presented as means, standard deviations, ranges, skewness, and kurtosis. Differences between the sexes were assessed with the two-sample t-test. Results: The average sagittal spinal shape was C3 - 12.9° - C7 - 43.0° - T10 - 27.1° - L5 for men and C3 - 12.1° - C6 - 44.5° - T11 - 34.1° - L5 for women. Men showed a significantly smaller thoracic kyphosis and lumbar lordosis curvatures than women. The average curvature due to the lateral deviation in the frontal plane was 6.1° for both sexes, the curvature was larger than 10° in 9.1% of men and 8.8% of women. We found left lateral deviation in 72.5% of men and in 63.6% of women. Conclusions: The study provides characteristics of the spine shape in a large sample of healthy young adults. Such characteristics should be part and parcel of determining the cut-off level for physiological spinal shape. Based on the results of the study, we suggest a lateral deviation of 10° as the maximum for a curvature to be still considered non-pathological.